Top Emission Organic Light Emitting Diodes Fabricated on Stainless Steel Foil - Fuh-Shyang Juang; Yu-Hsin Tuan; Hong-Kai Chen; Min-Chieh Lin; Hung-Lun Lin; Jun-Lin Huang (IEEE Access)
This study presents the fabrication and optimization of top-emitting organic light-emitting diodes (TEOLEDs) on stainless steel (SS) substrates, aiming to address challenges in surface roughness, hole injection efficiency, and light extraction. Due to the dual-sided conductivity of SS foil, a solution-type organic material (TOC 100) was spin-coated as an insulating and planarization layer, reducing the surface roughness from 8.61 nm to 0.46 nm, as measured by atomic force microscopy (AFM). The device structure was SS/Al/HATCN/TAPC/BH-08(host):OD-01(dopant)/TPBi/LiF/Al/Ag, with electro-optical characteristics comparable to TEOLEDs on glass substrates. However, the current density was slightly lower due to the roughness of the aluminum anode. The device optimizations included adding a gold layer (3 nm) to the aluminum anode, which increased hole injection efficiency and improved luminance from 4.99 cd/m2 to 24.65 cd/m2 at 14 V when the hole transport layer (TAPC) thickness was reduced from 20 nm to 10 nm. Adjusting cathode thicknesses (Al/Ag at 6/8 nm versus 12/10 nm) enhanced light output significantly, with luminance increasing from 9.5 cd/m2 to 24.7 cd/m2 at 15 V. Furthermore, using Ytterbium/Silver (Yb/Ag) cathodes improved current efficiency to 6.3 cd/A at 8 V compared to 4.5 cd/A for Liq/Al/Ag cathodes. Encapsulation extended TEOLED lifetime from 365 minutes to 490 minutes for luminance decay from 800 to 400 cd/m2. Flexibility tests demonstrated that the TEOLEDs maintained functionality under bending radii of 0.5 cm with brightness of 142 cd/m2 at 5 V. Additionally, thermal imaging revealed superior heat dissipation on SS substrates compared to glass substrates, with backside temperatures of $24.6~^{° }$ C versus $33.9~^{° }$ C when biased at 10 V.